An Operation Optimization Strategy of the Combined Power Generation System with Wind Power & Pumped Storage Based on Improved Whale Algorithm - LI Kecheng; YANG Ning (Kongzhi Yu Xinxi Jishu)
In order to overcome the randomness and intermittency of wind power generation and maximize the use of wind energy, a power generation system combined with wind power generation and pumped storage is constructed. Aiming at its operation optimization problem, this paper comprehensively considers the utilization of wind energy, the impact on power grid and overall economic benefits, takes the maximization of wind power utilization, the minimization of grid connected power fluctuations and the maximization of the economic benefits of combined power generation as the optimization objectives, considers the constraints such as power balance of generator units and power grid, and establishes a three-objective optimization model of the wind power & pumped storage combined power generation system. In order to solve the model, based on the basic whale optimization algorithm, a multi-objective whale optimization algorithm is developed by adding external population and leader selection mechanism, and the control parameter in the algorithm is improved to obtain an improved multi-objective whale optimization algorithm. Simulation results show that the convergence, distribution and uniformity of the improved multi-objective whale optimization algorithm are better than the multi-objective particle swarm optimization algorithm and the basic multi-objective whale optimization algorithm, which verifies the effectiveness and superiority of the proposed improved multi-objective optimization method. Select the appropriate solution from the obtained optimal solution set to obtain the operation optimization strategy of the combined power generation system, which can achieve better economic benefits and maximum wind energy utilization while smoothing the system output power.